Phenomenological Studies: The Nursing Manager Experience to Manage Nursing Staff During A Pandemic - Widyastuti, Dwi; Nurjannah, Misbah (Universitas Aisyah Pringsewu, 2022)
The increase in cases of COVID-19 patients in hospitals increases the demand for human resource management, one of which is the nursing staff. Management of nursing staff, especially during a pandemic very necessary because the mismanagement of nursing staff can add to the heavier nurse's workload, causing stress and fatigue that affect nurse performance to patient safety. The goal of this study to explore the experiences of nursing managers in managing nursing staff during a pandemic. A qualitative phenomenological research design was used in this study. Four nursing managers were selected using purposive sampling and the participants from three COVID-19 which three referral hospitals and one unreferral hospital. The participants were interviewed about their experiences via zoom and a semi-structured interview guide. Four themes were developed: (i) Maximizing the ward, (ii) Nursing schedule adjustment, (iii) New staff recruitment, and (iv) Nursing staff maintenance. Hospital readiness, especially in the nursing field, is needed to prepare several policies that can be operationalized in the face of unexpected events such as the COVID-19 pandemic, as well as regular training for all nursing staff in hospitals to be prepared both scientifically and practice in dealing with disease outbreaks to decrease anxiety. Abstrak: Meningkatnya kasus pasien COVID 19 di rumah sakit meningkatkan tuntutan manajemen sumber daya manusia, salah satunya adalah tenaga keperawatan. Pengelolaan tenaga keperawatan khususnya pada masa pandemi sangat diperlukan karena salah urus tenaga keperawatan dapat menambah beban kerja perawat yang semakin berat sehingga menimbulkan stres dan kelelahan yang mempengaruhi kinerja perawat terhadap keselamatan pasien. Tujuan dari penelitian ini adalah untuk mengeksplorasi pengalaman manajer keperawatan untuk mengelola staf keperawatan selama pandemi. Desain penelitian yang digunakan kualitatif fenomenologis. Empat manajer keperawatan dipilih secara purposive sampling dan partisipan berasal dari tiga rumah sakit rujukan COVID-19 satu rumah sakit yang bukan rujukan. Para peserta diwawancarai tentang pengalaman mereka melalui zoom meet dan panduan wawancara semi terstruktur. Empat tema berhasil dikembangkan yaitu: (i) Memaksimalkan bangsal, (ii) Penyesuaian jadwal keperawatan, (iii) Rekrutmen staf baru, dan (iv) Pemeliharaan staf keperawatan. Kesiapan rumah sakit khususnya di bidang keperawatan diperlukan untuk mempersiapkan beberapa kebijakan yang dapat dioperasionalkan dalam menghadapi kejadian yang tidak terduga seperti pandemi COVID-19, serta pelatihan rutin bagi seluruh tenaga keperawatan di rumah sakit untuk dipersiapkan baik secara keilmuan maupun praktek dalam menangani wabah penyakit untuk mengurangi kecemasan.